2017
DOI: 10.1007/s00253-017-8547-3
|View full text |Cite
|
Sign up to set email alerts
|

Production of ethylene glycol or glycolic acid from D-xylose in Saccharomyces cerevisiae

Abstract: The important platform chemicals ethylene glycol and glycolic acid were produced via the oxidative D-xylose pathway in the yeast Saccharomyces cerevisiae. The expression of genes encoding D-xylose dehydrogenase (XylB) and D-xylonate dehydratase (XylD) from Caulobacter crescentus and YagE or YjhH aldolase and aldehyde dehydrogenase AldA from Escherichia coli enabled glycolic acid production from D-xylose up to 150 mg/L. In strains expressing only xylB and xylD, 29 mg/L 2-keto-3-deoxyxylonic acid [(S)-4,5-dihydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 54 publications
2
51
0
1
Order By: Relevance
“…Considering that the isobutanol production pathway in SR8-Iso is compartmentalized in the mitochondria, it is likely that increased mitochondrial biogenesis is a major contributor to the enhanced isobutanol yields from xylose we observe. However, other physiological changes induced by xylose that could divert flux from ethanol to isobutanol production may still be taking place, which would be consistent with several examples where engineered biosynthetic pathways are enhanced by xylose utilization without involving their compartmentalization in mitochondria (S. K. Kim, Jo, Park, Jin, & Seo, 2017;Koivistoinen et al, 2013;Kwak, Kim et al, 2017;Salusjärvi et al, 2017;Turner et al, 2015). Future research to elucidate what physiological changes brought by xylose are responsible for this product biosynthesis enhancement may provide new insights to engineer strains with improved bioconversion of glucose into isobutanol and other nonethanol products.…”
supporting
confidence: 73%
“…Considering that the isobutanol production pathway in SR8-Iso is compartmentalized in the mitochondria, it is likely that increased mitochondrial biogenesis is a major contributor to the enhanced isobutanol yields from xylose we observe. However, other physiological changes induced by xylose that could divert flux from ethanol to isobutanol production may still be taking place, which would be consistent with several examples where engineered biosynthetic pathways are enhanced by xylose utilization without involving their compartmentalization in mitochondria (S. K. Kim, Jo, Park, Jin, & Seo, 2017;Koivistoinen et al, 2013;Kwak, Kim et al, 2017;Salusjärvi et al, 2017;Turner et al, 2015). Future research to elucidate what physiological changes brought by xylose are responsible for this product biosynthesis enhancement may provide new insights to engineer strains with improved bioconversion of glucose into isobutanol and other nonethanol products.…”
supporting
confidence: 73%
“…Our results demonstrate that the efficient recycling of NAD + and the addition of divalent metal ions (we showed Mn 2+ was the most effective) are crucial for pathway performance in the enzyme cascade and in cell-free extract assays, pointing at XAD and XDH/KGSADH as steps in the pathway that are sensitive to experimental conditions. Flux limitation via XAD was recently suggested in a combinatorial approach with a mixed in-vitro enzyme cascade, and this limitation has been attributed to insufficient FeS cluster building essential for dehydratases of the ILVD (isoleucine valine biosynthesis dehydratase)/EDD (Entner-Doudoroff dehydratase) enzyme family 33,51 . Therefore, in metabolic engineering approaches in yeast that suffer from low XAD activity, either the iron uptake was improved 27 or the FRA2 gene encoding an iron regulon repressor was deleted to induce FeS metabolism and thus improve XAD performance 26,51 .…”
Section: Discussionmentioning
confidence: 99%
“…Flux limitation via XAD was recently suggested in a combinatorial approach with a mixed in-vitro enzyme cascade, and this limitation has been attributed to insufficient FeS cluster building essential for dehydratases of the ILVD (isoleucine valine biosynthesis dehydratase)/EDD (Entner-Doudoroff dehydratase) enzyme family 33,51 . Therefore, in metabolic engineering approaches in yeast that suffer from low XAD activity, either the iron uptake was improved 27 or the FRA2 gene encoding an iron regulon repressor was deleted to induce FeS metabolism and thus improve XAD performance 26,51 . In their optimized yeast strain ((Δfra2, XylB, 4x(xylD, xylX and ksaD)) 26 , the authors observed low D-xylose consumption with D-xylonate excretion leading to acidification of the growth medium in shake flasks and oxygen deficiency was suggested as a possible reason for low efficiency of the oxidative Weimberg pathway.…”
Section: Discussionmentioning
confidence: 99%
“…This monomer is characterized by a hydrophilic and polar character, which allows an affinity for the aqueous phase [5]. Summarizing, ethylene glycols and their polymers are used in an enormous range of products and attract considerable interest in many branches of industry and science [6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%